STUDY OF GENETIC VARIABILITY IN CHICKPEA GERMPLASM AND ITS CONTRIBUTION TOWARDS GENETIC ADVANCEMENT - CHEEMA, KL; SARDAR, S; AMIN, MA; HUSSAIN, A; IQBAL, J; BATOOL, A; MUNIR, T; AKBAR, S; RASOOL, I; AZIZ, A; MAJEED, T (Biological and Clinical Sciences Research Journal, 2024)
Genetic variability is a pre-requisite to develop novel varieties in crop plants and to strengthen crop breeding programs at Research institutes. For this purpose, the genetic variability of nineteen chickpea genotypes was evaluated at Pulses Research Institute Faisalabad, Ayub Agricultural Research Institute during the Rabi season 2020-2021. The data were analyzed using D2 statistics, measured coefficient of variation, range, and standard deviation of various morphological traits of genotypes expressed significant value of variability. Seven principal components (PC) were extracted from the data by principal component analysis. Eigenvalues of the first two components were recorded>1 pointing out that these components have a major share in genetic variability. Data also expressed that no. of pods per plant (0.47) and root length (0.48) and plant height (0.48) and root length have the highest positive contribution of PC1 and PC2 respectively. In cluster - 1V genotypes with higher yield potential were grouped, therefore the members of cluster- 1V (D19025, D-19029, D-19036, and Bittle-2016) possessing higher grain yield along with sufficient amount of genetic diversity that can be incorporated into the genetic improvement program of chickpea.